Sanje: Izbrano delo Lermontova - Marina Bajić; Kočan Šalamon, Kristina; Kaloh Vid, Natalia (2015)
Dreams: Selected Work of Lermontov. The monograph entitled Dreams: Lermont's Selected Work is the result of months of work by students of the Department of Translation Studies at the Faculty of Arts, University of Maribor, who, with the support and encouragement of mentors from the department, undertook a challenging translation project. They have translated some of Lermont's most famous poetry masterpieces, such as Demon, Sail, Three Palms, Angel, Death of the Poet, and others. The editors also included Lermont's prose in the selection, the first part of the poet's famous novel, A Hero of Our Time, entitled White. Translations offer an insight into Lermont's rich treasure trove of creativity as they span the entire period of the poet's creation. The contribution of translations to Slovenian translation is certainly not negligible. Although Lermont has translated and translated into Slovenian many translators, the most famous of whom is Mile Klopčič, the translations have not been updated for some time. Lermont's updated translations may also reach those readers who do not yet know this important representative of Russian romance. The monograph outlines the directions to be followed by future generations of students of translation studies, as the translator learns his / her work primarily through practice. In any case, it is no more satisfying for a literary translator to see his work reach a wide range of readers and acquaint them with the spirit of a foreign culture.